Endocrine and Metabolic Effects of Adipose Tissue in Children and Adolescents - KOTNIK, Primož (Zdr Varst, 2015)
Adipose tissue is implicated in many endocrine and metabolic processes. Leptin was among the first identified adipose-secreted factors, which act in an auto-, para- and endocrine manner. Since leptin, many other adipose tissue factors were determined, some primarily secreted from the adipocytes, some from other cells of the adipose tissue. So-called adipokines are not only involved in obesity and its complications, as are insulin resistance, type 2 diabetes and other components of the metabolic syndrome, but also in growth, reproduction, bone metabolism, immune response, cancer development and many other important biological processes. Research in the field of adipokines has revealed new insights into the physiological and pathophysiologal processes and opened new therapeutic possibilities. In the present article, a special emphasis is devoted to research in children and adolescents.